Tratamento da infecção por Dioctophyme renale via nefrectomia em cães: em busca do estado da arte - Caye, Pâmela (2022)
Infection by Dioctophyme renale is called dioctophymatosis, a chronic and degenerative disease that commonly leads to irreversible destruction of the renal parenchyma. Known as the “giant kidney worm”, the nematode D. renale is reddish in color and reaches up to 100 cm in length, with a natural predilection for the right kidney. It is often diagnosed in dogs in the south of the Brazil, through techniques of urinalysis and abdominal ultrasound. The surgical procedure is recommended in the treatment of infection, since the disease does not respond to usual antiparasitic therapies. Often, affected patients present with total destruction of the renal parenchyma, being submitted to therapeutic nephrectomy. Although there are several reports of surgeries for the treatment of parasitosis, there are no studies in the current literature with large groups of patients and consolidation of therapeutic recommendations for parasitized dogs. Hyperbaric oxygen therapy (HBOT) is a therapeutic modality based on the provision of 100% oxygen in a hyperbaric environment, which is on the rise in Veterinary Medicine. Studies suggest its participation in reducing inflammatory stress, stimulating healing, potentiating antimicrobials and also in renal and hepatic protection against ischemia and reperfusion events. Thus, the objective of this study was to gather surgical cases of dogs naturally parasitized by D. renale and submitted to surgical therapy, using conventional and video-surgical techniques. Also, to analyze the action of hyperbaric oxygen therapy in two parasitized dogs, submitted to two sessions of 2 ATA for 30 minutes, as surgical preconditioning. Article 1 gathered 52 dogs with D. renale in the right kidney submitted to conventional nephrectomy, 61.5% of which were asymptomatic. The interval between diagnosis and surgery was 27.4±23 days and there was no surgical emergency. The right paracostal abdominal approach was more frequent and intraoperative complications occurred in 9.6% of the procedures. The mean postoperative survival was 835.5±428 days. Article 2 reported the case of two dogs submitted to two sessions of HBOT before performing therapeutic nephrectomy. Patients presented varied results, with improvement in the red series and decline in fibrinogen in case 1 and decline in the red series and increase in fibrinogen in case 2. On the other hand, the white series and platelet counts decreased in both cases. Article 3 describes the application of laparoscopic nephrectomy in 15 dogs performed in seven Brazilian institutions. Three techniques for accessing the abdominal cavity were described, with the most frequent use of portals with a triangular arrangement on the right flank. The most used form of hemostasis was the application of titanium clips in the renal hilum. The procedures were effective in all patients and allowed the removal of the kidney and parasites, being a technique highly recommended by the authors. It is concluded that the surgical therapy of dioctophymatosis is safe and applicable and that the disease is not characterized as a surgical emergency. HBOT is potentially beneficial in stabilizing patients with dioctophymosis.